2017
DOI: 10.1002/ptr.5863
|View full text |Cite
|
Sign up to set email alerts
|

Synergy between Auraptene, Ionizing Radiation, and Anticancer Drugs in Colon Adenocarcinoma Cells

Abstract: Colorectal cancer is a growing health concern with increasing mortality rates, and resistance to anticancer drugs and radiotherapy is a serious drawback in its treatment. Auraptene is a natural prenyloxycoumarin with valuable anticancer effects. The aim of current study was to determine the synergy between auraptene, ionizing radiation, and chemotherapeutic drugs in colon adenocarcinoma cells for the first time. To do so, HT29 cells were treated with combination of auraptene + cisplatin, + doxorubicin, or + vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 30 publications
0
17
0
Order By: Relevance
“…Assessment of cell viability revealed that non-toxic auraptene significantly increased cytotoxicity of hyperthermia, specifically 24 h after heat shock induction. Although it has been previously indicated that auraptene improved cytotoxicity of anticancer drugs in skin, esophageal and cervical cancers (Kleiner-Hancock et al 2010;Saboor-Maleki et al 2016;Nabekura et al 2008), and also enhanced toxicity of ionizing radiation in colon adenocarcinoma cells (Moussavi et al 2017), this is the first report on improved efficacy of hyperthermia by this coumarin derivative.…”
Section: R a F Tmentioning
confidence: 72%
See 3 more Smart Citations
“…Assessment of cell viability revealed that non-toxic auraptene significantly increased cytotoxicity of hyperthermia, specifically 24 h after heat shock induction. Although it has been previously indicated that auraptene improved cytotoxicity of anticancer drugs in skin, esophageal and cervical cancers (Kleiner-Hancock et al 2010;Saboor-Maleki et al 2016;Nabekura et al 2008), and also enhanced toxicity of ionizing radiation in colon adenocarcinoma cells (Moussavi et al 2017), this is the first report on improved efficacy of hyperthermia by this coumarin derivative.…”
Section: R a F Tmentioning
confidence: 72%
“…To assess cell viability upon combinatorial treatment, HT29 cells were pretreated with non-toxic auraptene for 3 consecutive days, and then subjected to hyperthermia. Since determined IC 50 of auraptene in HT29 cells was 39 µg/ml after 72 h (Moussavi et al 2017), 10 and 20 µg/ml auraptene, and 0.4% DMSO (relevant control), were administrated in these experiments. As shown in Figure 1, a significant (p<0.01) decrease in cell viability was observed when 20 µg/ml auraptene was used for 72 h, and cells were recovered for 12 h after heat shock induction.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The synergistic effects of AUR and CDDP can significantly increase the expression of tumor suppressor proteins and enhance the cytotoxicity as reported in previous studies. 2 , 9 , 10 However, the poor water solubility of AUR leads to low bioavailability and little delivery to the target site, while the severe renal toxicity and low selectivity of CDDP make prioritizing chemotherapy for cancers a challenge. 3 , 11 Referring to the advantages of a carrier-free drug delivery system, 12 two biodegradable materials, β-cyclodextrin derivatives (mono-(6-amino-mono-6-deoxy)-β-CD, CD) and hyaluronic acid (HA), were selected as carriers in this experiment to load AUR and CDDP against breast cancer, overcoming the problems of solubility, selectivity, and system toxicity.…”
Section: Introductionmentioning
confidence: 99%